2017
DOI: 10.1371/journal.pone.0176910
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-induced neuroprotection against glutamate excitotoxicity is mediated by the reduction of [Ca2+]i overload and NF-κB activation

Abstract: Prolactin (PRL) is a peptidic hormone that displays pleiotropic functions in the organism including different actions in the brain. PRL exerts a neuroprotective effect against excitotoxicity produced by glutamate (Glu) or kainic acid in both in vitro and in vivo models. It is well known that Glu excitotoxicity causes cell death through apoptotic or necrotic pathways due to intracellular calcium ([Ca2+] i) overload. Therefore, the aim of the present study was to assess the molecular mechanisms by which PRL main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…More specifically, the dam presents a significant local up‐regulation of antiapoptotic protein Bcl‐2 levels compared to dioestrus virgin rats under basal conditions, and lower cell death (FJC) and apoptosis (terminal deoxynucleotidyl transferase dUTP nick end labelling), no significant loss of neurones (NeuN), lower astrogliosis, and reduced microglial response (GFAP and Iba1 fluorescence levels and Scholl morphometric analysis of individual astrocytes) after both peripheral and central administration of KA . Some of these effects are attributed to PRL, which is highly expressed during lactation and has been shown to have protective effects in both in vivo and in vitro experiments …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the dam presents a significant local up‐regulation of antiapoptotic protein Bcl‐2 levels compared to dioestrus virgin rats under basal conditions, and lower cell death (FJC) and apoptosis (terminal deoxynucleotidyl transferase dUTP nick end labelling), no significant loss of neurones (NeuN), lower astrogliosis, and reduced microglial response (GFAP and Iba1 fluorescence levels and Scholl morphometric analysis of individual astrocytes) after both peripheral and central administration of KA . Some of these effects are attributed to PRL, which is highly expressed during lactation and has been shown to have protective effects in both in vivo and in vitro experiments …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, we demonstrate for the first time that parental in- 13,14 Some of these effects are attributed to PRL, which is highly expressed during lactation and has been shown to have protective effects in both in vivo [23][24][25] and in vitro experiments. 26,27 Hormones of reproduction, in particular PRL, have been considered to play a significant role in the expression of paternal behaviour in mammals; for example, various species show higher circulating levels of PRL after birth or contact with their offspring. 28 .…”
Section: Interaction With the Pups And Dam But Not The Pregnant Femmentioning
confidence: 99%
“…Hyperpolarisations in SFO neurones following PRL application may be the result of an increase in the activity of Ca 2+ ‐dependent K + channels, as is observed in Chinese hamster ovary cells following 4 nmol L ‐1 PRL application . Furthermore, experiments on cultured hippocampal neurones showed that PRL application increased intracellular Ca 2+ levels; this may also lead to an increase in Ca 2+ ‐dependent K + channel activation. An additional channel contributing to depolarisations in SFO neurones may be TRP as functional TRP channels are found in the SFO and PRL has been shown to increase TRP channel activation .…”
Section: Discussionmentioning
confidence: 99%
“…We performed the immunocytochemistry for all treatments according to the methodology of [42]. Briefly, K562 cells were cultured in round, glass coverslips and treated with MABB for 18 h and incubated with polyclonal antibodies of anti-Bax (1 : 100), anti-Bak (1 : 100), and anti-Bcl-2 (1 : 100) (Santa Cruz Biotechnology) overnight at 4°C.…”
Section: Immunofluorescence Of Bak Bcl-2 and Baxmentioning
confidence: 99%